Job Tension Growth and Emotional Intelligence in Challenge-Based Learning. Issue 3 (3rd April 2021) - Román-Calderón, Juan Pablo; Aguilar-Barrientos, Sara; EstebanEscalante, Juan; Arias, Alejandro; Barbosa, Jaime
Abstract: This paper presents a study that aims to identify the trajectory of job tension during a challenge-based learning (CBL) activity and study the role of student workgroup emotional intelligence in such a context. More longitudinal research on student stress is deemed necessary. The authors used Karasek's demand-control model (1979), collected longitudinal data (gathered at ten time points) from a 73-member team participating in an international student competition, and analyzed the data using the latent growth model approach. To the authors' knowledge no research has used panel data with multiple time points to explore the trajectory of job tension during a challenge-based learning activity. The findings indicate that the job tension of teams participating in a challenge-based learning activity has a quadratic rate of change, and that student work group emotional intelligence predicts individual differences with respect to team-level job tension. Practical implications include actions to improve the implementation of CBL tasks and to better deal with job tension and emotional intelligence in working groups.